Eggs, final-instar caterpillars and metamorphosis of cyclosia macularia guérin méneville (lepidoptera: zygaenidae) from its larval host plant baccaurea motleyana - Tan Li Peng; A.S. Sajap; A.S. Samsuddin (2015)
Information on the immature stages of Zyganidae moths is rather limited compared to that on the adults. An encounter with the caterpillars on the Baccaurea motleyana tree enabled a description of the eggs, final-instar caterpillar and characteristic cocoon of the Chalcosiine Day-flying Moth, Cyclosia macularia Guérin-Méneville, accompanied by illustrations. Sexual dimorphism of this species based on the adults is also described.